Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Pada PT. Lea Sanent Cabang Mall Bintaro - Widya Candra Dewi (Peneliti.net, 2020)
This study aims to determine the effect of product quality on purchasing decisions at PT. Lea Sanent, Bintaro Mall Branch. The method used is explanatory research with a sample of 78 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable product quality obtained an average score of 3.514 with good criteria. The purchase decision variable obtained an average score of 3.801 with good criteria. Product quality has a positive and significant effect on purchasing decisions with the regression equation Y = 11.869 + 0.744X, and the correlation coefficient value of 0.774 or has a strong level of relationship with a determination value of 59.9%. Hypothesis testing obtained a significance of 0.000 <0.05.